Cohesivity of Hyaluronic Acid Fillers. Issue 4 (October 2015) - Sundaram, Hema; Rohrich, Rod J.; Liew, Steven; Sattler, Gerhard; Talarico, Sergio; Trévidic, Patrick; Molliard, Samuel Gavard
<x xml:space="preserve">Abstract</x> Background: Biophysical characteristics of hyaluronic acid gel fillers reflect individual manufacturing processes. They confer rheologic properties that provide scientific rationale with Evidence Level II clinical correlation for selection of appropriate fillers for specific clinical applications. Cohesivity, a key property, maintains gel integrity, contributes to tissue support with natural contours, and diminishes surface irregularities. In this publication, a new, standardized visual assay for hyaluronic acid cohesivity is presented, applied, and discussed. Methods: Colored hyaluronic acid gel specimens were automatically extruded under standardized conditions into sterile water stirred at a constant rate. Based on 90 digital images showing ratios of intact to dispersed gel during assay of 10 Communauté Européenne–marked fillers, the five-point visual Gavard-Sundaram Cohesivity Scale was developed. Six plastic surgeons and dermatologists performed pilot validation of the scale, subsequently used to evaluate six U.S. Food and Drug Administration–approved fillers. Results: Validation of the Gavard-Sundaram Cohesivity Scale showed substantial repeatability and interrater consistency. Mean cohesivity scores from three assays of each tested filler showed significant differences. Cohesivity was high for Cohesive Polydensified Matrix (Belotero Balance), medium-high for Hylacross (Juvéderm Ultra 2/Ultra XC and Ultra 3/Ultra Plus XC), low-medium for Vycross (Juvéderm Voluma), and low for non–animal-stabilized hyaluronic acid (Restylane and Perlane). Conclusions: An evidence-based approach requires clinical corroboration of in vitro data. This new, reproducible cohesivity assay may have value together with elasticity (G') and viscosity measurements to understand and leverage distinct tissue distribution patterns and clinical behaviors of different hyaluronic acid products. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.